2008
DOI: 10.1007/s11738-008-0183-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrofusion of protoplasts from Solanum tuberosum, S. bulbocastanum and S. pinnatisectum

Abstract: This paper discusses a number of experiments performed, involving the fusion by an electric field of mesophyll protoplasts from Solanum tuberosum cv. Bintje, S. tuberosum dihaploid clones 243, 299 and the wild tuberous disease-resistant species S. bulbocastanum and S. pinnatisectum. Three fusion experiments (S. bulbocastanum + S. tuberosum dihaploid 243, S. pinnatisectum + S. tuberosum cv. Bintje and S. pinnatisectum + S. tuberosum dihaploid 299) yielded 542 calli, the 52 ones of which produced shoots. Obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
1
14
0
1
Order By: Relevance
“…In our experiment, somatic hybrids C-13 (?) S. etuberosum were confirmed on the different criteria, as in earlier reports, such as RAPD (Rokka et al 1994;Thieme et al 1997;Naess et al 2001;Barone et al 2002;Szczerbakowa et al 2003;Greplova et al 2008), SSR (Nouri-Ellouza et al 2006;Gillen and Novy 2007; (Thieme et al 1997;Maciejewska et al 1999;Oberwalder et al 2000;Horsman et al 2001;Szczerbakowa et al 2003;Greplova et al 2008), and phenotypic assessment (Novy and Helgeson 1994a;Thieme et al 2008;Szczerbakowa et al 2003;Greplova et al 2008). Confirmation of somatic hybrids was revealed by species-specific diagnostic bands (RAPD and SSR) from both the parental components.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In our experiment, somatic hybrids C-13 (?) S. etuberosum were confirmed on the different criteria, as in earlier reports, such as RAPD (Rokka et al 1994;Thieme et al 1997;Naess et al 2001;Barone et al 2002;Szczerbakowa et al 2003;Greplova et al 2008), SSR (Nouri-Ellouza et al 2006;Gillen and Novy 2007; (Thieme et al 1997;Maciejewska et al 1999;Oberwalder et al 2000;Horsman et al 2001;Szczerbakowa et al 2003;Greplova et al 2008), and phenotypic assessment (Novy and Helgeson 1994a;Thieme et al 2008;Szczerbakowa et al 2003;Greplova et al 2008). Confirmation of somatic hybrids was revealed by species-specific diagnostic bands (RAPD and SSR) from both the parental components.…”
Section: Discussionsupporting
confidence: 64%
“…Symmetric protoplasts fusion between potato and S. brevidens was used to integrate virus and aphids resistance (Valkonen et al 1992a, b;Polgar et al 1999). In many experiments, somatic hybrids have been produced between cultivated potato and wild species such as S. tarnii (Thieme et al 2008), S. etuberosum (Novy and Helgeson 1994a, b;Chavez et al 1988;Gavrilenko et al 2003;Novy et al 2002Novy et al , 2007Gillen and Novy 2007;Thompson et al 2007), S. pinnatisectum (Szczerbakowa et al 2005;Greplova et al 2008), S. bulbocastanum (Szczerbakowa et al 2001;Greplova et al 2008), S. berthaultii (Bidani et al 2007), S. nigrum Zimnoch-Guzowska et al 2003), S. circaeifolium (Oberwalder et al 2000), and S. acaule for transferring various biotic and abiotic resistance traits. In future, because of the continuous threat of phytopathogens, the introduction of new resistant germplasm to increase genetic diversity of potato gene pool is of vital need.…”
Section: Introductionmentioning
confidence: 99%
“…vubhb.cz/_te.asp?f=institute/06dogr.htm (Greplová et al 2008). The fusion combination gave 220 regenerants tested by flow cytometry (http://lmcc.ieb.cz/book/analysis-ploidylevel, Doležel and Göhde 1995) and subsequently by random amplification of polymorphic DNA (RAPD) (Greplová et al 2007(Greplová et al , 2008. This method confirmed that 31 of the 220 were somatic hybrids.…”
Section: Plant Materialsmentioning
confidence: 87%
“…The parental genotypes were taken from the Potato Gene Bank at Potato Research Institute Havlíčkův Brod, Ltd.; the somatic hybrids were obtained using symmetric somatic hybridization according to the protocol described at http://www. vubhb.cz/_te.asp?f=institute/06dogr.htm (Greplová et al 2008). The fusion combination gave 220 regenerants tested by flow cytometry (http://lmcc.ieb.cz/book/analysis-ploidylevel, Doležel and Göhde 1995) and subsequently by random amplification of polymorphic DNA (RAPD) (Greplová et al 2007(Greplová et al , 2008.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation